Statistical data science - Adams, Niall M.; Cohen, Edward (World Scientific Publishing Europe Ltd., 2018)
As an emerging discipline, data science broadly means different things across different areas. Exploring the relationship of data science with statistics, a well-established and principled data-analytic discipline, this book provides insights about commonalities in approach, and differences in emphasis. Featuring chapters from established authors in both disciplines, the book also presents a number of applications and accompanying papers--Provided by Publisher.